«ΑΙΔΩΣ»: A Moral and Political Virtue in Ancient Spartan Education - Dellis, John (Études helléniques / Hellenic Studies, 1999)
The notion of αιδώς had been considered a fundamental moral and political virtue in all ancient Greek societies. This notion was treated by all ancient Greek poets and philosophers and has been researched today in most of them, especially in Homer and Hesiod. This brief article intends to explore the notion and its function in ancient Spartan education, a study which has not been done so far. For the Spartans, aidôs was the foundation of their education and their consequent loyalty to societal life.